2022
DOI: 10.1093/ntr/ntac071
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Nicotine Reduction Policy in the United States: A Qualitative Study

Abstract: Introduction Several countries are considering a reduced nicotine policy that would make cigarettes minimally or non-addictive. This qualitative study documents reactions to the policy that should be addressed by future communication efforts. Methods In 2020, we recruited participants in Atlanta, GA and San Francisco, CA (27 people who exclusively smoke, 25 who dual use cigarettes and e-cigarettes, 32 who formerly smoked, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…16 Some people who smoke even believe that nicotine reduction will substantially increase smoking among current smokers via compensatory behaviours (ie, smoking more to get the same levels of nicotine as from regular cigarettes), cause relapse among former smokers and encourage non-smokers to try cigarettes. 15 Misperceptions about VLNCs and reduced nicotine policy may be diminished through messaging. Both empirical and theoretical literature indicate that effective messages can influence motivations to try novel behaviours, including smoking, and therefore may enhance the policy's effect on quitting behaviour 25 26 while conveying the harmfulness of VLNCs and bolstering attitudes towards policies.…”
Section: Original Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…16 Some people who smoke even believe that nicotine reduction will substantially increase smoking among current smokers via compensatory behaviours (ie, smoking more to get the same levels of nicotine as from regular cigarettes), cause relapse among former smokers and encourage non-smokers to try cigarettes. 15 Misperceptions about VLNCs and reduced nicotine policy may be diminished through messaging. Both empirical and theoretical literature indicate that effective messages can influence motivations to try novel behaviours, including smoking, and therefore may enhance the policy's effect on quitting behaviour 25 26 while conveying the harmfulness of VLNCs and bolstering attitudes towards policies.…”
Section: Original Researchmentioning
confidence: 99%
“…21 22 Public perceptions of the FDA's scientific accuracy and integrity may influence how the policy is construed, or even the level of opposition against such a policy. 15 VLNC communication strategies may be strengthened by integrating source information. Prior research has shown that the public is generally uninformed about the role of the FDA in tobacco regulation 34 but that those who smoke, despite scepticism, still find the FDA to be generally trustworthy.…”
Section: Implications For Communicating About the Vlnc Policymentioning
confidence: 99%
See 3 more Smart Citations